Dispersion mechanism of coal water slurry prepared by mixing various high-concentration organic waste liquids. (1st March 2021) - Wang, Shuangni; Liu, Jianzhong; Pisupati, Sarma V.; Li, Dedi; Wang, Zhihua; Cheng, Jun
Graphical abstract: Highlights: High concentration organic waste liquids was investigated to reduce clean water consumption. Mixing two types of organic waste liquids that are insoluble in each other evenly. The total interaction energy in the entire WCWS system is greater than 0. The steric stabilization energy is introduced into the system by xanthan gum. Xanthan gum serves as a bridge in the system based on its molecular characteristic. Abstract: High-concentration organic waste liquids have complex components and their treatment is difficult. These liquids also contain hydrophobic organic pollutants. The preparation of waste liquid coal water slurry (WCWS) can aid with environmental protection and resource utilization. In this study, xanthan gum was selected from 11 types of additives because it overcomes the problem of solution incompatibility during the mixing of various high-concentration organic waste liquids. The experimental results showed that with 0.08 wt% addition of xanthan gum, no stratification occurred in the mixed waste liquid and the apparent viscosity of the WCWS was 921.1 mPa ∙ s. In this study, the role of xanthan gum was studied, and the effect of its addition on the coal particle surface was characterized by zeta potential and contact angle measurement. In addition, various interaction energies in the WCWS system were calculated using the extended DLVO theory. The results showed that xanthan gum introduced steric hindrance interaction energy into the WCWS system, enabling the system to be stably dispersed.